Relationship between Adverse Childhood Experiences and Resiliency among College Students - Glory Okwori (Journal of Epidemiology and Public Health, 2021)
Background: Adverse childhood experiences (ACEs) are associated with negative outcomes, however, there are factors that can mitigate the effects from exposure to ACEs. This study examined the prevalence of adverse childhood experiences (ACEs), characteristics of resilient individuals and the association between ACE scores, resiliency and other factors among college students. Subjects and Method: A cross-sectional survey was completed in 2018. Frequencies were calculated for the number and types of ACE experienced by participants. Bivariate relationships between characteristics of participants and resilience were examined using Chi-square tests. The independent relationship between ACE scores and resiliency factors was examined using ordinal logistic regression. The dependent variable was ACE score. An ordinal logistic regression model examined the relationship between conventional ACE scores and resilience levels and other factors. Results: There were 570 study participants. Seventy-one percent of study participants had experienced at least one conventional ACE, and 98% had experienced at least one expanded ACE. Individuals with high resilience had lower conventional ACE scores and better health. Females (OR= 1.67; 95% CI= 1.14 to 2.45) were more likely to have higher conventional ACE scores. Participants living in suburban areas compared to rural areas (OR= 0.61; 95% CI: 0.43 to 0.85), and children raised with both parents compared to single parents (OR= 0.17; 95% CI= 0.12 to 0.25) were less likely to have higher conventional ACE scores. Gender (OR= 0.54; 95% CI= 0.35 to 0.82) and general health status (OR= 1.50; 95% CI= 1.05 to 2.13) were the only significant predictors of the expanded ACE scores. Conclusion: Findings identify important resilient traits such as relationships, self-control, internal beliefs, and initiative,. as well asportray the high prevalence ofACEs and the importance of resilience as a protective factor in reducing ACEs.